Supercritical CO2 Extraction of Bioactive Compounds from Sarawak Black Pepper: Experimental, Solubility Modeling, and Kinetic Studies - Obek, Christine Ann (Curtin University, 2024)
This study investigates the solubility of Sarawak Black Pepper in supercritical carbon dioxide (SC-CO2) across different operating conditions by performing experimental works and modeling studies. It is envisaged that the findings (solubility data and model) from this research will be useful to facilitate the transition of lab-scale extraction into pilot-testing extraction, ultimately paving the way for industrial-scale production of Sarawak Black Pepper-based value-added products.